Quipus and Witches' Knots The Role of the Knot in Primitive and Ancient Culture, with a Translation and Analysis of "Oribasius de Laqueis" - Day, Cyrus Lawrence (University Press of Kansas, 1967)
This essay in cultural anthropology provides a comprehensive view of the way primitive people in all parts of the world once utilized knots; mnemonic knots-to record dates, numbers, and cultural traditions; magic knots-to cure diseases, bewitch enemies, and control the forces of nature; and practical knots-to tie things and hold things together.In his discussion of mnemonic knots, the author analyzes the Peruvian quipus (or knotcalendars and knotrecords) and suggests that the Inca astronomerpriests, known to have been accurate observers of the movements of the planets, may also have been able to predict the dates of lunar eclipses; and he shows how it is possible to manipulate the Ina abacus in accordance with the decimal system.His treatment of magic knots includes instances from Babylonian times to the present, with curious examples of the supernatural power attributed to the Hercules knot (i.e., the square knot) in Egypt, Greece, and Rome. His analysis of a littleknown treatise on surgeons' slings and nooses, written by the Green physician Heraklas, is the first detailed account of the specific practical knots used by the ancient Greeks and Romans.Quipus and Witches' Knots, which is abundantly illustrated, often surprises the reader with the unexpected ways in which the once universal dependence of men on knots has left its mark on the language, customs, and thought of modern peoples.